2020
DOI: 10.1021/acsnano.0c02699
|View full text |Cite
|
Sign up to set email alerts
|

Super-Resolution Fluorescence Imaging Reveals That Serine Incorporator Protein 5 Inhibits Human Immunodeficiency Virus Fusion by Disrupting Envelope Glycoprotein Clusters

Abstract: Serine incorporator protein 5 (SERINC5) is the host antiretroviral factor that reduces HIV-1 infectivity by incorporating into virions and inhibiting the envelope glycoprotein (Env) mediated virus fusion with target cells. We and others have shown that SERINC5 incorporation into virions alters the Env structure and sensitizes the virus to broadly neutralizing antibodies targeting cryptic Env epitopes. We have also found that SERINC5 accelerates the loss of Env function over time compared to control viruses. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
79
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(86 citation statements)
references
References 57 publications
7
79
0
Order By: Relevance
“…Based on the observation that SERINC5 did not codistribute with Env the authors conclude that its effect in clustering is indirect, and hypothesize that its effect could be based on sequestering of viral membrane chol by SERINC5. [ 62 ] Our results directly support the hypothesis that sequestering of chol by SERINC5 would remove the molecular switch driving Env redistribution and hamper entry.…”
Section: Discussionsupporting
confidence: 78%
“…Based on the observation that SERINC5 did not codistribute with Env the authors conclude that its effect in clustering is indirect, and hypothesize that its effect could be based on sequestering of viral membrane chol by SERINC5. [ 62 ] Our results directly support the hypothesis that sequestering of chol by SERINC5 would remove the molecular switch driving Env redistribution and hamper entry.…”
Section: Discussionsupporting
confidence: 78%
“…As a result, most reports focus on Nef's ability to antagonize SERINC5, and its impact on SERINC3 remains relatively understudied. While the mechanism of SERINC's antiviral activity has not been fully clarified, a recent study found that SERINC5 disrupts viral Envelope (Env) clusters on the virion surface through an indirect process [18]; however, other studies suggest that a direct interaction between Env and SERINC5 may result in conformational changes to Env that impair its function [19,20]. Regardless of the precise mechanism(s) of action, by removing SERINC proteins from the infected cell surface, Nef reduces their incorporation into virions and counteracts their antiviral function [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Whereas isoforms Serinc3 and Serinc5 can block infection of subsequent cells, other isoforms, including Serinc2, do not. Previous work has suggested that Serincs may act at the very earliest steps of membrane fusion by changing the conformation or clustering of unliganded Env (14), as evidenced by increased binding of broadly neutralizing antibodies to Env on Serinc5-containing viral particles (15)(16)(17). Serincs are integral membrane proteins that have been reported to be involved in lipid synthesis (12).…”
mentioning
confidence: 99%